1985
DOI: 10.1212/wnl.35.7.1063
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole is ineffective in the treatment of amyotrophic lateral sclerosis

Abstract: Fifty-nine patients with amyotrophic lateral sclerosis participated in a 12-month, double-blind crossover trial. The patients were given either levamisole 150 mg or placebo in identical tablets once a week orally, and a rating of neurologic signs and symptoms was recorded on monthly visits. The patients were crossed over at 6 months. Levamisole had no effect on the rate of score decline in the 20 patients who completed the trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Levamisole has strong immunomodulatory activity [27][28][29]. Early in its development large-scale clinical research programs tested the effect of levamisole in human diseases caused by impaired cellular immune mechanisms, including ALS where the drug was ineffective [11]. More promising results were obtained in a small trial of multiple sclerosis patients [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levamisole has strong immunomodulatory activity [27][28][29]. Early in its development large-scale clinical research programs tested the effect of levamisole in human diseases caused by impaired cellular immune mechanisms, including ALS where the drug was ineffective [11]. More promising results were obtained in a small trial of multiple sclerosis patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is used outside the U.S. in humans and has been used as an adulterating agent in illicit street drugs [10]. Levamisole has been used in an ALS clinical trial in which the drug was administered once a week for 6 months; no benefit was observed [11]. Here, we have conducted a 14 week dosing study of these two drugs in the SOD1 G93A and Prp-TDP43 A315T models of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Many other clinical trials were conducted using immunomodulating agents [64,[79][80][81][82], agents modulating the cholinergic activity [83,84], antiviral agents [85,86], and gangliosides [87,88].…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…Anti-inflammatory/ immunomodulatory Inosiplex [65], Tilorone [66], Gangliosides [67], Levamisole [68], Ciclosporin [69], IFN-a [70], Transfer factor [71], Cyclophosphamide [72], Thalidomide [73], IFN-ß-1a [74], Minocycline [75], Glatiramer acetate, ONO-2506PO Antioxidants/bioenergetics Acetylcysteine [76], Co-enzyme Q10 [77], Tamoxifen, Selegiline [78], Glutathione [79], Delta 9-Tetrahydrocannabinol Creatine monohydrate, Vitamin E, KNS-760704, MCI-186…”
Section: Introduction To the Compoundmentioning
confidence: 99%